2019
DOI: 10.1096/fj.201900815rr
|View full text |Cite
|
Sign up to set email alerts
|

Controlled induction and targeted elimination of p16INK4a‐expressing chondrocytes in cartilage explant culture

Abstract: Cellular senescence is a phenotypic state that contributes to age‐related diseases through the secretion of matrix‐degrading and inflammatory molecules. An emerging therapeutic strategy for osteoarthritis (OA) is to selectively eliminate senescent cells by initiating apoptosis. This study establishes a cartilage explant model of senescence induction and senolytic clearance using p16Ink4a expression as a biomarker of senescence. Growth‐factor stimulation of explants increased the expression of p16Ink4a at both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 62 publications
2
28
0
Order By: Relevance
“…Senolysis has been proved very useful to efficiently remove the senescent cells from live organs and beneficial results had been reported in many diseases such as osteoarthritis, atherosclerosis, diabetics, and so on [7,[32][33][34][35][36][37]. Jeon et al reported that UBX0101, a smallmolecule senolytic, could effectively induce senescent chondrocytes toward apoptosis and attenuate the progression of OA in both posttraumatic and age-related spontaneous OA model [7].…”
Section: Discussionmentioning
confidence: 99%
“…Senolysis has been proved very useful to efficiently remove the senescent cells from live organs and beneficial results had been reported in many diseases such as osteoarthritis, atherosclerosis, diabetics, and so on [7,[32][33][34][35][36][37]. Jeon et al reported that UBX0101, a smallmolecule senolytic, could effectively induce senescent chondrocytes toward apoptosis and attenuate the progression of OA in both posttraumatic and age-related spontaneous OA model [7].…”
Section: Discussionmentioning
confidence: 99%
“…Lysates were also generated from mouse embryonic fibroblast (MEF) cultures established from p16 INK4a intact (MEF2) and p16 INK4a /p19 Arf−/− germline‐knockout (MEF6) mice. These MEF samples had previously been used as positive and negative controls for assessing p16 INK4a by immunoblotting . The immunoblots were stained with a total protein stain (catalog no.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, the senolytic action of ABT-263 appears to depend on inhibition of BCL-X L and/or BCL-W, while BCL-2 inhibition is dispensable [84,86]. Similar to D+Q, ABT-263 was successful in eliminating senescent cell populations in several disease models including aging-associated bone loss [87], radiation-induced lung fibrosis [88], lung emphysema [89], uterine leiomyoma [90], tau-dependent neurodegenerative disease [91], radiation-induced neurodegeneration [92], myocardial infarction (including ischemia-reperfusion injury) [93,94], heart failure [95], pulmonary hypertension [96], insulin resistance [97], osteoarthritis [98,99], synthetic implant-mediated fibrosis [100], and Duchenne muscular dystrophy [101]. ABT-263 is currently a cornerstone in preclinical studies of senolysis and remains a promising drug for use against both liquid and solid tumors [102][103][104].…”
Section: Senolytic Therapies: Have We Hit Gold or Pyrite? 21 Establmentioning
confidence: 99%